FC 126IMPACT OF POLYCLONAL ANTI-T-LYMPHOCYTE IMMUNOGLOBULINS ON THE RECURRENCE OF IGA NEPHROPATHY AFTER KIDNEY TRANSPLANTATION: THE PIRAT STUDY. (29th May 2021) - Maillard, Nicolas; Kamar, Nassim; Hourmant, Maryvonne; Morelon, Emmanuel; Le Quintrec, Moglie; Pouteil-Noble, Claire; Frimat, Luc; Caillard, Sophie; Ducloux, Didier; Merville, Pierre; Buchler, Matthias; Albano, Laetitia; et al.
Abstract: Background and Aims: IgA Nephropathy (IgAN) often recurs on kidney transplants, accounting for a significant specific kidney failure occurrence after ten years of transplantation vintage. Polyclonal anti-T-lymphocyte antibodies (PATLA) immunosuppressive induction has been shown to be associated with a lower rate of IgAN recurrence compared to basiliximab and no induction in a retrospective study. The aim of the PIRAT study was to compare an induction by PATLA versus basiliximab by the mean of a randomized controlled trial. Method: Adults with biopsy-proven primary IgAN as primary cause of end stage of renal disease, first transplantation, panel reactive antibody <50% could be included in the study. Patients were randomized 1:1 prior to transplantation to receive either PATLA (Grafalon, 4mg/kg for 3 days, then two days 3mg/kg) or basiliximab (20mg at transplantation and 4 days after). Both groups received methylprednisolone followed by oral corticoids for at least one year, tacrolimus and mycophenolic acid. Primary outcome was the clinico-histological recurrence defined by both IgA deposition on transplant biopsy and albuminuria>300mg/d during 5 years post-transplantation. Protocol biopsy at 5 years was highly recommended. Results: A total of 117 patients were finally included in 13 French transplant centers, with 60 patients in the PATLA group and 57 in the basiliximab control group. Both groups were similar (median, PATLA vs. basiliximab, p>0.05 wilcoxon test) in term of sex ratio (4.45 vs 4.57), recipient age (47.9 vs. 47.7 years old), dialysis vintage (26.2 vs. 24.6 months), age at IgAN diagnosis (35.0 vs. 42.2 years old), cold ischemia (780 min vs 682 min), warm ischemia (34 vs. 36.1min), proportion of living donors (33% vs. 25%). The 5-year protocol biopsy was performed on 48% vs. 45% of patients, with overall proportion of patients evaluated by at least one biopsy of 63% vs. 66%. A trend in favor to the protection by PATLA from the occurrence of a clinico-histological recurrence was found (hazard ratio, univariate Cox model 0, 35 [0.11-1.1], p=0.082). Biopsy proven histological recurrence was significantly lower after PATLA induction (HR 0.34 [0.16-0.76], p=0.0079). PATLA group experienced more infections (40 vs. 28 p=0.06), a lower number of graft losses (3 vs 9, p=0.07), a lower number of biopsy-proven acute rejections (5 vs 10, p=0.17). Similar rates of cytomegalovirus and BK virus infections were found. Conclusion: PATLA for immunosuppressive induction was found protective from the recurrence of IgA deposition during the first 5 years after transplantation, compared to basiliximab. A similar trend, although not significant, was found about the clinico-histological recurrence which was the predefined primary outcome.